CREATIVE ADS STRATEGY OF BLANJA.COM TO WIN E-COMMERCE MARKET THROUGH YOUTUBE - Velda Ardia; Fanisah Nur Fadilah (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
Today’s business competition among e-commerce companies heating up, Blanja.com compete with other aggres- sive e-commerce in advertising. The right advertising creative strategy is required. In that regard, the mentioned- creative advertising strategy uses one of social media asset namely Youtube. The purpose of this study is to ana- lyze the creative advertising strategy of one of the e-commerce in Indonesia, Blanja.com on Youtube as well as to identify  the  reasons  of  using  Youtube  behind  its  creative  advertising  strategies.  Relevant  theories  of  this  study consist of advertising theory, creative advertising strategies, new media, youtube and e-commerce. This research method  uses  descriptive  qualitative  with  data  collection  through  interviews.  In  the  research  there  was  one  key informant namely the Blanja.Com Brand Manager, as well as three other informants for data triangulation. They are all advertising practitioners from Bujukrayu agency, Harsi Lima Agency, dan dari Morzel Digital. The results showed that the Blanja.Com advertisement version of "The Period of Gak Blanja" which was aired on Youtube featured generic strategies advertisement, which featured product differentiation and service differentiation. But it is found that there is a differentiation of communication content, namely some words used as key words , such as words of “Masa Iya Gak Blanja” and “Homoblanjanicus”. The word not only became the attraction of advertise- ment but also a punchline from other e-commerce ads. The message to be conveyed by this advertisement is peo- ple need shopping, and Blanja.com offers various attractive alternative shopping options. The use of Youtube is considered an effective tool to advertise, in particular the segmentation of Blanja.Com is the millennial generation with an age range of 25-35 years.Keywords: Advertising, Creative Advertising Strategy, E-Commerce, Youtube